Optimization of logistics distribution costs using the NWCR, MODI, and stepping stone methods - Fristi Riandari; Hengki Tamando Sihotang; Hikmah Adwin Adam; Afrisawati Afrisawati (Jurnal Mantik, 2026)
Logistics distribution is a crucial component of the supply chain that impacts a company's operational efficiency. Inaccuracy in allocating goods distribution can increase transportation costs and reduce the effectiveness of distribution services. Therefore, an optimization method capable of producing a distribution pattern with minimum costs is needed. This study aims to analyze the optimization of logistics distribution costs using the North West Corner Rule (NWCR), Modified Distribution Method (MODI), and Stepping Stone methods in determining optimal distribution solutions. The study uses a quantitative approach with a transportation model. The research data include distribution costs, supply capacity, and demand from several warehouses to the distribution area. The initial solution was obtained using the NWCR method, then its optimality was tested using the MODI and Stepping Stone methods. The analysis was carried out by comparing the total distribution costs generated by each method. The results showed that the NWCR method produced an initial solution with a total distribution cost of Rp154,000,000. After optimization using the MODI and Stepping Stone methods, the total distribution cost was successfully reduced to Rp128,500,000, or a savings of 16.56%. The MODI and Stepping Stone methods yield the same optimal solution, but the MODI method has a more efficient iteration process. The combination of the NWCR, MODI, and Stepping Stone methods has been proven to improve the efficiency of a company's logistics distribution costs. This approach can be used as an alternative decision-making tool for optimizing goods distribution and effectively managing the supply chain